Comparison of Dexamethasone and Tramadol as Adjuvant to Levobupivacaine in Supraclavicular Block - Manu Seth; Rajeev Das; Rubal Singhal (Academia Anesthesiologica International, 2020)
Background: Supraclavicular block is one of the most effective anaesthetic procedures in an operation of upper extremity. The present study was conducted to evaluate and compare dexamethasone and tramadol as adjuvant to levobupivacaine in supraclavicular block. Subjects and Methods: The present study was conducted in the department of Anaesthesiology. It comprised of 50 patients of American Society of Anaesthesiologists (ASA) grade I and II of age group 18 - 60 years of either sex. Group I (n=25) in which 30 ml of 0.5% levobupivacaine hydrochloride plus 2 ml tramadol (100mg) was used. Group II (n=25) in which 30 ml of 0.5% Levobupivacaine hydrochloride plus 2 ml dexamethasone (8 mg) was used. In both groups, sensory block, motor block and complications were recorded. Results: The mean duration of sensory block in group I was 13.41 hours and in group I was 15.28 hours, motor block was 14.52 hours in group I and 17.45 hours in group II and duration of analgesia was 16.15 hours in group I and 19.26 hours in group II. The difference was significant (P< 0.05). Common complication recorded was intravascular injection, hoarseness, hypotension and bradycardia in both groups. The difference was significant (P< 0.05). Conclusion: Dexamethasone is a better adjuvant than tramadol when added to levobupivacaine in supraclavicular brachial plexus block.